Draft Eighth Five Year Plan 1990-95 Government of Rajasthan - Planning Commission (Planning Commission, 1990)
Prior to integration, Rajasthan was a conglomeration of 19 princely States and 3 chiefships varying in size, population, administrative efficiency and socio-economic development. After independence, the process of integration of princely States began in 1948 and the final shape of the present State was affected by the merger of Ajmer and reorganisation of States in 1956. The State of Rajasthan has 27 administrative districts, subdivided into 207 tehsils and 237 development blocks. the total area of the State is 3.42 lakh sq. kms.
Government of Rajasthan, Planning Department